2017
DOI: 10.1097/inf.0000000000001609
|View full text |Cite
|
Sign up to set email alerts
|

Measles Cases in Children Requiring Hospital Access in an Academic Pediatric Hospital in Italy, 2008–2013

Abstract: Hospitalizations of children with measles continue to occur in European areas where elimination has not been achieved. Children with chronic diseases represent a vulnerable population that is at higher risk of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Complications such as bronchopneumonia or encephalitis (one of the leading causes of death in developing countries) often contribute to deaths from measles [ 6 , 41 - 44 ]. In the PICU, hospitalization lasted an average of 7.1 days compared to 4.5 days in the general ward, consistent with previous reports [ 34 , 36 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Complications such as bronchopneumonia or encephalitis (one of the leading causes of death in developing countries) often contribute to deaths from measles [ 6 , 41 - 44 ]. In the PICU, hospitalization lasted an average of 7.1 days compared to 4.5 days in the general ward, consistent with previous reports [ 34 , 36 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the hospitalization rate was relatively high at 88.9%. It is worth noting that rates of hospitalization as low as 20% or as high as 70% have been observed in other studies [ 36 - 39 ]. We found that children under four years old were determined to be three times more likely to be hospitalized than older children.…”
Section: Discussionmentioning
confidence: 74%
“…There was need for PICU admission in 1.9% of children due to severe complications, such as ARDS, sepsis and altered mental status and there was one death. Need for ICU hospitalization and deaths especially in children with underlying diseases have also been described in other studies in developed countries [2,29,36].…”
Section: Plos Onementioning
confidence: 57%
“…In our setting, the proportion of measles cases reported by hospital wards was unexpectedly high, although this was not necessarily related to the presence of clinical complications. In this regard, however, it must be stressed that hospitalized patients were significantly younger than the cases in the community [ 21 23 ], most of them were children aged ≤5 years, and this may have potentially reflected a justifiable high-level attention in respect to this population group.…”
Section: Discussionmentioning
confidence: 99%